Recovery of Gold in Au/Cu/Mg System from SH/Fe3O4@SiO2 as a Magnetically Separable and Reusable Adsorbent - Qomariyah, Ani; Nuryono, Nuryono; Kunarti, Eko Sri (Indonesian Journal of Chemical Research, 2021)
The recovery of Au(III) in the Au/Cu/Mg system from mercapto-silica hybrid coated magnetite (SH/Fe3O4@SiO2) adsorbent has been investigated. This adsorbent characterized using FT-IR to determine functional groups, crystallinity study using XRD, surface morphology using SEM, material compositions with XPS, surface area using nitrogen adsorption, and TGA to study thermal stability. Adsorption of metal ions carried out with batch system for 30 minutes at a pH of 3. In the Au/Cu/Mg multi-metal system, Au(III) ions were easily desorbed (approximately 85%) by SH/Fe3O4@SiO2 adsorbent based on HSAB (Hard Soft Acid Base) theory that Au(III) ion is a softer metal than Cu(II) and Mg(II) where Au(III)>Cu(II)>Mg(II). The recovery of Au(III) ions was easily desorbed using thiourea 7% in 0,1 M HCl solution with the percentage of 79%. The process of SH/Fe3O4@SiO2 adsorbent separation after adsorption and recovery was very easy. The adsorbent could perfectly separate in 5 minutes using an external magnet. The SH/Fe3O4@SiO2 adsorbent can be reused on the adsorption-desorption process of Au(III) in the Au/Cu/Mg system approximately four times of cycle reactions.